Kajian penyesuaian program pengajian UPSI dengan bidang pekerjaan (graduan 1999-2009) - Kasa Zakaria, Ibrahim Mohamad, Kahar Mohd Ramli Buyong, Dawi Amir Hasan, Hashim Ahmad, Che Omar Che Mohd Zulkifli, Che Ngah Mohamad Suhaily Yusri, Oth (Universiti Pendidikan Sultan Idris, 2010)
Kajian penyesuaian program pengajian UPSI dengan bidang pekerjaan (graduan 1999-2009) by Kasa Zakaria, Ibrahim Mohamad, Kahar Mohd Ramli Buyong, Dawi Amir Hasan, Hashim Ahmad, Che Omar Che Mohd Zulkifli, Che Ngah Mohamad Suhaily Yusri, Oth